Migration of the Northern Boundary of the East Asian Summer Monsoon Over the Last 21, 000 years. Issue 17 (3rd September 2021) - Wu, Beilei; Lang, Xianmei; Jiang, Dabang
Abstract: Investigating the past evolution of the northern boundary of the East Asian summer monsoon (EASM) is important in understanding the East Asian climate of the past, present, and future. In this study, using a set of transient simulations from TraCE‐21ka, we investigate the migration of the EASM northern boundary over eastern China via three metrics and its responses to individual external forcings during the last 21, 000 years. The northern boundary was located farther southeastward from 21 ka to 18 ka and more northwestward since 15 ka compared with the present boundary. For two key time slices, the boundary exhibited a southeastward migration ranging from 120 to 140 km in the last glacial maximum (LGM) and a 110–140 km northwestward shift in the mid‐Holocene relative to the present boundary. Temporally, the evolution of the boundary was characterized first by a poleward migration and then an equatorward shift from the LGM to the present, which was mainly driven by orbital insolation. This long‐term trend was punctuated by several millennial fluctuations in response to meltwater fluxes. The boundary migration during the LGM and the mid‐Holocene generally lies within the range of the multimodel results from the Paleoclimate Modeling Intercomparison Project Phase 4 (PMIP4). In terms of dynamic mechanisms, an orbitally induced increase of summer insolation led to an enhanced land‐sea thermal contrast between the East Asian continent and adjacent ocean and, in turn, intensified low‐level southerly winds, which facilitated the northwestward migration of the EASM northern boundary and more precipitation over eastern China. The boundary responses to the changing meltwater fluxes were similar but weak. Additionally, the EASM northern limit was closely linked to the forest‐steppe boundary. The reconstructed forest‐steppe boundary estimated from pollen records and the simulated EASM northern edge display spatially consistent positions, orientations, and change trends. Key Points: The simulated northern boundary of the East Asian summer monsoon shows a 120–140 km southeastward retreat during the last glacial maximum and a 110–140 km northwestward advance during the mid‐Holocene compared with the present boundary The changes in the large‐scale meridional temperature gradient and land‑sea thermal contrast are the underlying dynamic mechanisms The reconstructed forest‑steppe boundary from pollen records and the simulated northern boundary of the East Asian summer monsoon show comparable positions, orientations, and change trends